In Vitro Characterization of Herpes Simplex Virus Type 1 Clinical Isolates with Respect to Their Potential as Gene Vectors - Orpana, Julius (My University, 2022)
Herpes simplex virus 1 (HSV-1) is a common human pathogen that can be found in approximately half of the population. Typically, it causes relatively mild symptoms such as cold sores, though HSV-1 can also enter a latent stage and become undetectable to the immune system, which allows it to persist in an individual for their entire life. However, HSV-1 is also one of the most promising candidates for gene therapy vector development as it possesses multiple beneficial properties that set it aside from other potential oncolytic viruses. These include the capability for repeated dosing, a well-established neurovirulence gene that can be deactivated, and the capacity to support large transgenes. Accordingly, the only currently available oncolytic virus approved in the western world is based on HSV-1 with multiple other vector prospects currently in clinical development. A set of 36 HSV-1 clinical strains isolated from patients was subjected to a panel of tests in order to determine their potential for further vector development. To this end, the strains were tested for multiple parameters, such as their replication characteristics, growth rates, oncolytic potential, and drug resistance. Several strains with promising results in view of oncolytic vector development could be identified, such as strains possessing significant oncolytic potential, high overall infectivity, or a significant tendency toward lateral spreading from cell to cell. While further testing will be required to make decisive conclusions, the results of this thesis serve as a useful baseline for future projects.
Keywords: Herpes Simplex Virus, gene therapy, oncolytic vector, clinical isolate, antivirals